2019
DOI: 10.1002/fsh.10260
|View full text |Cite
|
Sign up to set email alerts
|

Parentage‐Based Tagging: Reviewing the Implementation of a New Tool for an Old Problem

Abstract: Parentage‐based tagging (PBT), an innovative and large‐scale application of genetic parentage assignments, is transforming how fisheries managers determine the age and origin of sampled fish. PBT is an efficient alternative for mass tagging and has been widely implemented in the Pacific Northwest. While still an emerging technology, PBT is being used to provide information to managers in state, federal, and tribal agencies on the harvest, research, and conservation of Chinook Salmon Oncorhynchus tshawytscha an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
104
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(105 citation statements)
references
References 25 publications
1
104
0
Order By: Relevance
“…) and can confidently identify parent–offspring relationships with low rates of error when considering thousands of putative parents that are collected across large spatial scales (i.e., hatcheries throughout the Columbia River basin; Steele et al. ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…) and can confidently identify parent–offspring relationships with low rates of error when considering thousands of putative parents that are collected across large spatial scales (i.e., hatcheries throughout the Columbia River basin; Steele et al. ).…”
Section: Methodsmentioning
confidence: 99%
“…The parentage analysis was performed by using the maximum likelihood methods that are described by Anderson and Garza (2006) as implemented in SNPPIT (Anderson 2010). Previous work has demonstrated that PBT is highly accurate (Steele et al 2013) and can confidently identify parent-offspring relationships with low rates of error when considering thousands of putative parents that are collected across large spatial scales (i.e., hatcheries throughout the Columbia River basin; Steele et al 2019).…”
Section: Monitoring Juvenile Productionmentioning
confidence: 99%
“…Anderson and Garza (2006) noted that parentage‐based tagging (PBT) provided a method of identifying both the age and population of origin for individual salmon. PBT uses molecular‐based approaches to conduct large‐scale parentage assignments and has resulted in the unprecedented ability to identify genetically millions of hatchery‐origin salmonids to their hatchery of release and age (Steele, Hess, Narum, & Campbell, 2019). Steele et al.…”
Section: Introductionmentioning
confidence: 99%
“…Parentage-based tagging (PBT) in salmonids entails the genotyping of parental fish, typically the entire broodstock of one or more hatcheries, to enable the subsequent assignment of lethally and nonlethally sampled progeny back to their parents within the hatchery broodstocks (Anderson & Garza, 2006;Steele, Hess, Narum, & Campbell, 2019). Assignment of progeny to parents through standard exclusion or probability-based methods provides the age as well as the hatchery and family of origin for progeny sampled at any location or time throughout their lives.…”
Section: Introductionmentioning
confidence: 99%
“…Assignment of progeny to parents through standard exclusion or probability-based methods provides the age as well as the hatchery and family of origin for progeny sampled at any location or time throughout their lives. PBT techniques developed and validated for a number of Pacific salmonids are increasingly being used to provide comprehensive identification and assessment objectives (Beacham et al, , 2018Hess et al, 2016;Steele et al, 2019). Beacham et al (2019) demonstrated the utility of PBT for the aging and identification of southern BC hatchery coho salmon in highly mixed-stock fisheries throughout BC and in adult returns to rivers known as escapements (portion of a salmon population that does not get caught in fisheries and returns to its natal river to spawn).…”
Section: Introductionmentioning
confidence: 99%